Review and Analysis of Current Responses to Covid-19 in Brazil and India: Period of January to July 2020 - Raden Mas Try Ananto Wicaksono (International Journal of Social Science and Religion (IJSSR), 2020)
The COVID-19 pandemic is impacting emerging markets through an unprecedented mix of domestic and external shocks whose combined effects are very hard to predict. Through this analysis, the author would explore more regarding the government policy priorities in dealing with COVID-19 especially from the emerging countries. Brazil and India as the best countries to be weighed with Indonesia due to some similarities they have. The research method used in this research is a descriptive qualitative and comparative study, the types of comparable, in this case, are Most Different System Designs (MDSD). The results show that Brazil has a partial-lockdown system and India has a full-lockdown system, yet in both countries, there is a high number of death rates and confirmed cases. The politics of the moment are only a piece of the policy environment, however, economics as of a major factor. Thus, the paper suggests ensuring that the lockdown is not being lifted prematurely; it is crucial to significantly ramp up the capacity of the healthcare system.